Dysmenorrhea: effectiveness and acceptability of treatment with a drug containing 2 mg of chloromadinone acetate and 0.03 mg of ethinyl estradiol - V N Prilepskaia; A N Mgerian; E A Mezhevitinova (IP Berlin A.V., 2017)
According to various researchers, primary dysmenorrhea affects between 20% and 91% of women. Combined oral contraceptives (COCs) are the first choice drugs in young women with primary dysmenorrhea. They have high efficiency, therapeutic and protective effects. In order to assess the acceptability of a drug containing ethinylestradiol and chloromadinone acetate in women with symptoms of dysmenorrhea, 75 women aged 75 years were monitored at V.I.Kulakov Research Center for Obstetrics, Gynecology and Perinatology of the Ministry of Health of the Russian Federation. at the age of 18 to 40 years. The average age was 23.4±4.1 years. The average duration of the menstrual cycle is 27.4±1.3 years. The duration of dysmenorrhea averaged 6.3 years. All patients were prescribed the drug Belara in the classical mode (21+7). 54 (72%) patients noted the disappearance of symptoms already on the 3rd cycle of drug use and another 15-20% of patients in 12 months. Subjective evaluation, obtained with the help of visual analogue scale, showed that after 3, 6 and 12 months of using the drug Belara, 72, 80 and 92% of patients were respectively satisfied or very satisfied with the effect of therapy. Analysis of individual BP parameters before and during contraception testified to the lack of influence of this drug on these parameters. Analysis of the dynamics of biochemical parameters, lipid spectrum of blood and some parameters of hemostasis did not reveal clinically and statistically significant changes that go beyond the limits of normative values. Analyzed are also the side effects that arose on the background of using the drug Belara, which were observed mainly in the first 2 months use of COCs. Six patients noted meager intermenstrual bleeding, 3 women reported nausea, tension and heaviness in the mammary glands - 5 (6.7%), one woman complained of insignificant dizziness during 1 course of treatment. Allergic reactions were not identified. All the side effects disappeared on their own and did not require additional therapy. Contraceptive effectiveness of the drug Belara was 100%. Thus, literature data and our experience have shown that a combined oral contraceptive containing 2 mg of chloromadinone acetate and 0.03 mg of ethinyl estradiol (Belara) is a highly effective, safe and pathogenetically valid drug in the therapy of dysmenorrhea. With long-term use it does not have a negative effect on the cardiovascular system, parameters of hemostasis and metabolic metabolic rates. All women were from 18 to 39 years old with dysmenorrhea of varying severity.